Evaluating Digital Security Solutions for Online Gender-Based Violence Using a Multicriteria Decision-Making Approach - Aliu, F. M.; Bode, M. A. (Journal of Science, Technology and Innovation Research, 2026)
Digital security solutions are technologies and processes that help people stay safe online. Online gender-based violence (OGBV) is a major hindrance to online participation and security, especially among women and girls. The prevalence of cyber harassment, doxing, nonconsensual image sharing, and online stalking necessitates the urgent need for specific, gender-sensitive information security measures. The Preference ranking organization method for enrichment evaluation (PROMETHEE-II), a multi-criteria decision-making method was applied in this research to create an organized decision-support framework for evaluating and ranking possible online gender-based violence options. In order to ensure privacy, accessibility, and usability for victims and vulnerable users, five practical alternatives were chosen for evaluation: end-to-end encryption tools, AI-based content moderation systems, anonymous reporting platforms, digital literacy training programs, and emergency support applications. These alternatives were evaluated based on five factors: effectiveness, ease of use, anonymity, cost, and speed of response. The study evaluated solutions and produced a thorough rating using PROMETHEE-II, which applies preference functions and stakeholder-defined weights. The findings reveal that digital literacy awareness programs and emergency support apps had the best net flow scores of 0.160416667 and 0.045833333, demonstrating their greater capacity to strike a balance between user privacy, efficacy, and cost. The quantitative and replicable methodology used in this study can be used by policy makers, technologists, and digital rights advocates to evaluate gender-sensitive information security strategies and to rank and choose solutions that reduce OGBV and promote inclusive online safety.